"Posmaczki autentyczności". Elementy autobiograficzne w powieściach Michała Choromańskiego = "Flavors of authenticity". Autobiographical aspects in Michał Choromański`s novels - Kłos, Zdzisław (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Michał Choromański was from the generation of Witold Gombrowicz, Bruno Schulz and Czesław Miłosz. His novel "Zazdrość i medycyna" [Jealousy and Medicine] brought him great popularity in the 1930s. However, this pre-war popularity was not consolidated by numerous works published in the post-war period. It was only in the 1970s that his work began to be appreciated. His work was largely permeated with autobiographical elements. Choromański himself, however, claimed, somewhat perversely, that he absolutely hates autobiography.
Keywords: Choromański, Michał (1904-1972); autobiografizm; literatura polska; autobiography; Polish literature